Ergonomics Applied to Product Design: The Fashion Designers’ Point of View - Crislaine Gruber; Lizandra Garcia Lupi Vergara (GEPROS: Gestão da Produção, Operações e Sistemas, 2019)
Palavras-chave: Design do vestuário. Design de moda. Produto ergonômico. This paper aims to investigate the application of ergonomics in the fashion design process, from the designers’ point of view. We conducted semi-structured interviews with 19 designers. The interviews were recorded and transcribed for further content analysis, which was based on three categories: ergonomics concept; approach to ergonomics in academic training and professional experience; application of ergonomics in product development. It was found that most of the participants understand the concept of ergonomics and consider that it is currently?? applied in the fashion design process. However, we concluded that this application is intuitive. In addition, participants understand that the application of ergonomics and obtaining anthropometric data from users are activities developed only by patternmaking professionals. It is believed that it is necessary to approach ergonomics in the professional training of fashion designers to make this application systematic and effective, raising users' satisfaction and, consequently, increasing the competitiveness of companies.